Inclusive English Teaching Strategies at SLBN 1 Tanjungpinang: Blind vs deaf students - Nana Raihana Askurny; Firmansyah, Bianca Naluri; Andri Wijaya Ginting; Tasya Alkhaira; Wawan Ramdani; Syarifah Nazla Alqudsy (PANYONARA: Journal of English Education, 2025)
This study focuses on inclusive English teaching strategies for blind and deaf students at SLBN 1 Tanjungpinang, emphasizing that education must be ensured for all students, including those with special needs. The purpose of the study is to explore differentiated instructional approaches that align with the sensory modalities of each group to enhance learning outcomes. . Using a qualitative case study approach, the study employs field-based observations and reflective documentation as research methods. The study compares auditory and tactile strategies for blind students with visual-based methods for deaf students. The main findings indicate that blind students benefit from interactive storytelling, structured verbal activities, and tactile materials such as Braille, while deaf students gain from vocabulary modelling, sign language, and visual aids. The study concludes that adaptive pedagogy, tailored to sensory strengths, is critical for competency-based and inclusive English education in special schools, despite challenges like limited resources and the need for continuous teacher training.